Enhancing Young Learners’ Vocabulary Through Flashcards and Multimedia-Based Instruction - Fadhila, Eza; Fadilaturrahmah, Fadilaturrahmah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study investigates the effect of combined media videos, PowerPoint presentations, and flashcards on the vocabulary mastery of first-grade students at SD Islam Bunayya. A quasi-experimental design was applied, involving a control group and an experimental group, each consisting of 20 students. Data were collected using pretests, posttests, and questionnaires measuring vocabulary knowledge, spelling speed, and students’ enthusiasm. Instruments were validated using standard procedures in educational research, and reliability was assessed using Cronbach’s Alpha. The results show that students in the experimental group achieved greater improvement than those in the control group, with average scores increasing from 87.22 to 89.54. Students also demonstrated higher enthusiasm, faster spelling performance, and stronger vocabulary retention. Overall, the study indicates that combined multimedia supports improved vocabulary learning and enhances student engagement in early-grade English classrooms.